The molecular phenotype of kisspeptin neurons in the medial amygdala of female mice - Hatcher, Katherine M.; Costanza, Leah; Kauffman, Alexander S.; Stephens, Shannon B. Z. (Frontiers in Endocrinology, 2023)
Reproduction is regulated through the hypothalamic-pituitary-gonadal (HPG) axis, largely via the action of kisspeptin neurons in the hypothalamus. Importantly, Kiss1 neurons have been identified in other brain regions, including the medial amygdala (MeA). Though the MeA is implicated in regulating aspects of both reproductive physiology and behavior, as well as non-reproductive processes, the functional roles of MeA Kiss1 neurons are largely unknown. Additionally, besides their stimulation by estrogen, little is known about how MeA Kiss1 neurons are regulated. Using a RiboTag mouse model in conjunction with RNA-seq, we examined the molecular profile of MeA Kiss1 neurons to identify transcripts that are co-expressed in MeA Kiss1 neurons of female mice and whether these transcripts are modulated by estradiol (E2) treatment. RNA-seq identified >13,800 gene transcripts co-expressed in female MeA Kiss1 neurons, including genes for neuropeptides and receptors implicated in reproduction, metabolism, and other neuroendocrine functions. Of the >13,800 genes co-expressed in MeA Kiss1 neurons, only 45 genes demonstrated significantly different expression levels due to E2 treatment. Gene transcripts such as Kiss1, Gal, and Oxtr increased in response to E2 treatment, while fewer transcripts, such as Esr1 and Cyp26b1, were downregulated by E2. Dual RNAscope and immunohistochemistry was performed to validate co-expression of MeA Kiss1 with Cck and Cartpt. These results are the first to establish a profile of genes actively expressed by MeA Kiss1 neurons, including a subset of genes regulated by E2, which provides a useful foundation for future investigations into the regulation and function of MeA Kiss1 neurons.